Using The Important Performance Analysis To Improve Product and Service Attribute Performance in Regional-Owned Enterprise - Muchamad Bachtiar; Raden Isma Anggraini; Fithriyyah Shalihati (School of Business, IPB University (SB-IPB), 2020)
This study aimed to analyze the performance level and importance level according to customer perceptions as well as the priority of product and service attribute improvement. The data were analyzed using descriptive analysis of the Importance Performance Analysis (IPA) and Customer Service Index (CSI) approach with 1980 respondents out of 157,270 customers selected through Cluster Stratified and Systematical Unproporsional Sampling (CSUS) technique. The result showed that there was no product attribute with significantly low performance. It was supported by the CSI result with a value of 0.74, which meant SATISFACTORY or VERY GOOD. However, there were still negative gaps between the performance level and importance level, with an average value of 0.36. Product attribute (P2) water supply quality, (P3) water continuity, (P4, P5, and P6) water quality were quite a concern. This study also found a product attribute with a positive gap in (P7)water quality (sediment), which meant that this ROE could reallocate its utilized resources to improve other product attributes of concern. In terms of service attributes, there was no significant attribute that needed an immediate follow-up. It was supported by the overall CSI score of 0.76, which meant SATISFACTORY or VERY GOOD. Even so, service attributes were important and deserved attention in the aspects of (J2) bill payment process, (J6) the capability of call center officers and (J7) social media admins, and (J10) dispute settlement with customers. Five service attributes, which were (J1) administrative services, (J3) complaint services, (J4) fairness to obtain services, (J5) the capability of customer service officers, and (J11) service interruption information, were recommended to be reallocated to other service attributes that were more important. Keywords: customer satisfaction, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), regional-owned enterprise